Chitosan derivatives obtained by chemical modifications for biomedical and environmental applications - Alves, N. M. (2008)
Chitosan is a natural based polymer, obtained by alkaline deacetylation of chitin, which presents excellent biological properties such as biodegradability and immunological, antibacterial and wound-healing activity. Recently, there has been a growing interest in the chemical modification of chitosan in order to improve its solubility and widen its applications. The main chemical modifications of chitosan that have been proposed in the literature are reviewed in this paper. Moreover, these chemical modifications lead to a wide range of derivatives with a broad range of applications. Recent and relevant examples of the distinct applications, with particular emphasis on tissue engineering, drug delivery and environmental applications, are presented.